Automated Detection And Counting Of Pus Cells On Sputum Images - Rosyati, Hamid; Faradila, Naim; Nurul Wahidah, Arshad; Zeehaida, Mohamed (2013)
his paper discusses on a feature extraction of pus cell in sputum slide image. This invention is developed to analyze and count the content of cells specifically pus cell within a biological sample, and more particularly sputum sample which is useful for sputum quality grading. This pus cell detection is addressed by mean intensity and area for single and overlapping pus cells. It is found that mean intensity and area for single pus cell are ranges from 130-163 and 35-81 respectively. Whereas, with considering other elements exist in sputum image such as epithelial cells and artifacts, the mean intensity for overlapping pus cells are ranges from 130-45 with area of 65-300. This system has the sensitivity of 92.11%, with specificity of 81.82%, accuracy of 87.32% and precision of 85.37.